Análise econômica do direito e sua problemática constitucional / Economic Law Review and Its Constitutional Issue - Carvalho, Vinícius Soares (Revista do Programa de Pós-Graduação em Direito, 2015)
The Economic Analysis of Law , developed over the past centuries and consolidated in mid-Twentieth Century, centrally in the chairs of the Chicago School , whose main exponent is the American judge Richard Posner , proposes an innovative vision of legal institutions, backed by economic elements. This way of looking at the phenomenon of rights brings forth a conceptual problem, much in view of the theoretical common sense of lawyers accustomed to not face a speech that relativize its ideals of righteousness . It is necessary to recognize the thematic and methodological relevance of Economic Analysis of Law, especially the urgent need to adapt the constitutional reality of a judicial hermeneutics which implements not only individual interests but also makes possible substantial government prerogatives.